Human factors investigation of the behavioural response to cues of a fire emergency - Alhuthali, Abdullah (2021)
Safety is a significant priority in the contemporary building environment and a focus for many organisations and businesses. Studies have been conducted to review different factors regarding human behaviour during fire evacuation and to utilize the findings to model improved egress procedures and to train occupants on how to evacuate safely. However, much is still unknown about the processes of perceiving and responding to an emergency when cues from different information sources conflict. For example, when a fire evacuation warning has been issued, but the conditions in the area appear to be fine, some of the building occupants may have uncertainty about the correct action to take. There are several cues to an emergency, and some of these may not lead to optimum behaviour. For example, prior research has shown that, in cases where there has been a prevalence of nuisance alarms such as false alarms, occupants may not take action when a real fire alarm is sounded (Proulx, 2007). Moreover, cues to an emergency are often ambiguous and may not be immediately perceived as a threat.